Kompetensi Sumberdaya Manusia Pada Kesatuan Pengelolaan Hutan Produksi Di Lampung - Riska Ersi Noviyanti; Christine Wulandari; Rommy Qurniati (Jurnal Sylva Lestari, 2016)
Areas of Production Forest Management Unit (KPHP) Model has been established in Lampung that includes KPHP Register Model 47 Way Terusan Lampung Tengah regency, KPHP Bukit Punggur Lampung Tengah regency, KPHP Gedong Wani Lampung Selatan regency and KPHP Muara Dua Way Kanan regency (Wulandari, 2011). One of the sinifeant factor management KPHP is the competent human resources. Currently competence of human resources in KPHP especially in Lampung Province is not known yet, so it is necessary to do the mapping of human resources, which will be used as material for consideration on improving the competence of the employees KPHP in Lampung Province. The purpose of this research is to identify the competence of human resources that exist in every KPHP in Lampung and formulate the recommendations to increase the competence in need by KPHP in Lampung Province. The research was conducted in April 2014 in KPHP Gedong Wani Lampung Selatan regency and KPHP Way Terusan Lampung Tengah regency. Competence human resources in KPHP Gedong Wani in the field of forest planning of 49.15 % and in the field of the utilization of the forest of 28.33%. Competence human resources in KPHP Way Terusan in areas of forest planning is 35.07% and in the fields of the utilization of the forest of 36.33. Human resource competence in KPHP Gedong Wani and KPHP Way Terusan in Lampung Province, have different educational background like Forestry Senior High School, bachelor of Forestry of non-forestry, as well as Master of Forestry. Lack of training that followed, led to lack of forest planning and forest unilization within technical and non-technical. So they need training for employees in accordance with the needs of not-technical competence. Keywords: competence, human resources, production forest management unit